The oncogenic potential of NANOG: An important cancer induction mediator. Issue 4 (22nd September 2020) - Najafzadeh, Basira; Asadzadeh, Zahra; Motafakker Azad, Rohollah; Mokhtarzadeh, Ahad; Baghbanzadeh, Amir; Alemohammad, Hajar; Abdoli Shadbad, Mahdi; Vasefifar, Parisa; Najafi, Souzan; Baradaran, Behzad
Abstract: Cancer stem cells (CSCs) are a unique population in the tumor, but they only comprise 2%–5% of the tumor bulk. Although CSCs share several features with embryonic stem cells, CSCs can give rise to the tumor cells. CSCs overexpress embryonic transcription factor NANOG, which is downregulated in differentiated tissues. This transcription factor confers CSC's stemness, unlimited self‐renewal, metastasis, invasiveness, angiogenesis, and drug‐resistance with the assistance of WNT, OCT4, SOX2, Hedgehog, BMI ‐1, and other complexes. NANOG facilitates CSCs development via multiple pathways, like angiogenesis and lessening E‐cadherin expression levels, which paves the road for metastasis. Moreover, NANOG represses apoptosis and leads to drug‐resistance. This review aims to highlight the pivotal role of NANOG and the pertained pathways in CSCs. Also, this current study intends to demonstrate that targeting NANOG can dimmish the CSCs, sensitize the tumor to chemotherapy, and eradicate the cancer cells.